A recent paradigm on iron absorption, prevalence, and emerging dietary approaches to eradicate iron deficiency. Issue 1 (6th March 2023) - Malhotra, Umang; Roy, Mrinmoy; Sontakke, Manmath; Choudhary, Pintu
Abstract: Iron is an essential micronutrient required for growth and development during all stages of human life with the most important function of oxygen transportation via hemoglobin. With the prevalence of the triple burden of malnutrition in the world, there is an increase in iron deficiency anemia affecting a lot of people, especially the adolescent population of girls. The diagnosis of iron deficiency anemia is confirmed by low iron stores and decreased hemoglobin levels. It is prevalent in both urban and rural regions; however, gender differences exist which start from the age of 15 years, as females are more prone to develop iron deficiency. On comparing the 4th and 5th surveys conducted by the National Family Health Survey, India, it can be observed that the prevalence of anemia has increased which is a major cause of concern. One of the major reasons that people suffer from this deficiency would be vegetarianism. Plant sources contain iron but they are present in the ferric state which needs to be converted to the ferrous state. The bioavailability of plant sources is low therefore, this condition can be tackled by adopting steps like dietary diversification, biofortification, fortification, and supplementation. Abstract : This review deals with the metabolism of iron in the human body with various factors affecting iron absorption. This review aims to clarify the general problem IDA (Iron deficiency anemia) and provides dietary approaches to tackle this problem. Various strategies to treat iron deficiency are reviewed.